Risk Factors and Outcomes From All-Terrain Vehicle Injuries Compared With Motor Vehicle Collisions in Children. (October 2019) - Ramgopal, Sriram; Cramer, Natan; Gaines, Barbara A.; Conti, Kavitha A.
We compared risk factors and outcomes of children injured from all-terrain vehicle (ATV) injuries to those injured from motor vehicle collisions (MVC). We reviewed records of patients ≤18 years of age admitted to a trauma center with ATV- or MVC-related injuries between January 1, 2000, and December 31, 2015. Demographics were compared using logistic regression. Rates of injuries were compared using χ 2 tests. Of 6293 patients, 1140 (18%) ATV and 5153 (82%) MVC events were identified. In multivariable analysis (adjusted odds ratio [aOR], 95% confidence interval [CI]), patients with ATV-related injuries occurred more at older age (≥12 years; aOR = 4.29, 95% CI = 3.20-5.77), in rural counties (aOR = 3.72, 95% CI = 2.62-5.28), in regions with lower median household income (aOR = 1.37, 95% CI = 1.03-1.83), and in the spring (aOR = 2.44, 95% CI = 1.87-3.18), and summer (aOR = 2.50, 95% CI = 1.93-3.25) compared with winter. ATV-related injuries occurred less frequently among females (aOR = 0.76, 95% CI = 0.65-0.89). Upper extremity injuries were associated with ATV-related injuries ( P ≤ .001). Findings may facilitate identification of at-risk groups for targeted interventions.